Preclinical and Phase 1 Assessment of Antisense Oligonucleotide Bepirovirsen in Hepatitis B Virus–Transgenic Mice and Healthy Human Volunteers: Support for Clinical Dose Selection and Evaluation of Safety, Tolerability, and Pharmacokinetics of Single and Multiple Doses. Issue 10 (16th August 2022) - Han, Kelong; Theodore, Dickens; McMullen, Gina; Swayze, Eric; McCaleb, Michael; Billioud, Gaetan; Wieland, Stefan; Hood, Steve; Paff, Melanie; Bennett, C. Frank; Kwoh, T. Jesse
Abstract: Dose‐dependent reductions in hepatitis B virus (HBV) RNA, DNA, and viral proteins following bepirovirsen administration were observed in HepG2.2.15 cells. In HBV‐transgenic mice treated at 50 mg/kg/wk, hepatic HBV RNA and DNA were reduced by 90% and 99%, respectively. Subsequently, a phase 1 first‐in‐human study assessed pharmacokinetics and tolerability of single (75–450 mg) and multiple (150–450 mg on days 1, 4, 8, 11, 15, and 22) subcutaneous bepirovirsen doses in 96 healthy volunteers. Bepirovirsen at all dose levels was rapidly absorbed (maximum plasma concentration 3–8 hours after dosing), rapidly distributed to peripheral tissues, and slowly eliminated (median plasma terminal half‐life: 22.5–24.6 days across cohorts). Plasma exposure (dose‐proportional at 150–450 mg) and concentration‐time profiles were similar following the first and sixth doses, suggesting little to no plasma accumulation (steady state achieved by day 22). Renal elimination of full‐length bepirovirsen accounted for <2% of the total dose. Across the single and multiple dose cohorts, 197 treatment‐emergent adverse events were reported, with 99% and 65% classified as mild in severity and local injection site reactions, respectively. In conclusion, bepirovirsen showed an acceptable safety profile in humans with observed pharmacokinetics consistent with the chemical class, warranting further evaluation of bepirovirsen in chronic HBV infection.